Neighborhood social cohesion and physical disorder in relation to social isolation in older adults: racial and ethnic differences - Weidi Qin; Emily J. Nicklett; Jiao Yu; Ann W. Nguyen (BMC, 2024)
Abstract Background Neighborhood factors of social isolation have been understudied, hindering efforts to reduce social isolation at the neighborhood level. This study aims to investigate the longitudinal effects of neighborhood social cohesion and physical disorder on social isolation in community-dwelling older adults, as well as to examine whether race/ethnicity moderates the neighborhood-isolation relationship. Methods We used 11-year data from the National Health and Aging Trend Study, a longitudinal national study of Medicare beneficiaries aged 65 and older. Social isolation was measured through a summary score across four domains: marital/partner status, family and friend contact, religious attendance, and club participation. A series of weighted mixed-effects logistic regression models were performed to test the study aims. Sample sizes ranged from 7,303 to 7,291 across individual domains of social isolation. Results Approximately 20% of participants reported social isolation. Findings indicated a negative association between neighborhood social cohesion and social isolation. Higher levels of neighborhood social cohesion were longitudinally associated with lower odds of social isolation (odds ratio [OR] = 0.52, 95% CI: 0.47-0.58). Yet, the presence of neighborhood physical disorder was associated with an increased risk of overall social isolation ([OR] = 1.2, 95% CI: 1.00, 1.44). Race/ethnicity significantly moderated the effects of neighborhood social cohesion and physical disorder on social isolation. The odds of no in-person visits associated with neighborhood social cohesion are smaller among Black adults compared to White adults. Black adults had constantly lower odds of isolation from religious attendance compared to White adults regardless of the level of neighborhood social cohesion. Hispanic adults had decreased odds of having no friends associated with signs of physical disorder, while no associations were found among older White adults. White adults had higher odds of isolation from in-person visits when living in neighborhoods with signs of physical disorder, whereas no association was observed among older Black and Hispanic adults. Conclusions This study elucidates the role of neighborhood characteristics in shaping social isolation dynamics among older adults. Furthermore, the observed moderation effects of race/ethnicity suggest the need for culturally sensitive interventions tailored to address social isolation within specific neighborhood and racial contexts.